2013
DOI: 10.1007/978-3-642-39928-2_2
|View full text |Cite
|
Sign up to set email alerts
|

IT Governance in a Malaysian Public Institute of Higher Learning and Intelligent Decision Making Support System Solution

Abstract: IT governance in public universities is yet to be fully appreciated. This is because IT governance is just evolving as a new paradigm to take care of the stakeholders' expectations in leveraging IT with business goals. This study explores issues of IT governance and the use of IDMSS in a public university in Malaysia. The interviews and documents were analysed to generate themes. The findings show the need for effective IT governance in the university. This will enable optimal usage of IT resources, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…Organizations will find it difficult to refer to the personnel in-charge as no one will assume the responsibility for related issues without a structure in place [18]. Similar issues were reported as there was a lack of a platform for management to discuss IT-related issues [21].…”
Section: Structurementioning
confidence: 89%
See 4 more Smart Citations
“…Organizations will find it difficult to refer to the personnel in-charge as no one will assume the responsibility for related issues without a structure in place [18]. Similar issues were reported as there was a lack of a platform for management to discuss IT-related issues [21].…”
Section: Structurementioning
confidence: 89%
“…Miscommunication and improper guidelines led to a lack of coordination between departments and facilities regarding the utilization of IT resources. Guidelines and practices together with a reliable ITG structure prevent information disparity between the expectations of the CIO and implementation on the ground [21]. A study on Malaysia's public sector revealed that 76.19% of organizations had a low ITG maturity level.…”
Section: Guidelines and Practicesmentioning
confidence: 99%
See 3 more Smart Citations